Changes in Quality and Flavor of Chopped Chili Peppers in Ceramic Jars during Fermentation - WANG Hongwei, LIU Hongjuan, QIN Yeyou, XU na, HU Jialiang, YUAN Xiao, LIU Yang, JIANG Liwen (Shipin Kexue)
In order to investigate changes in the quality, flavor and major aroma components of pickled chilies in ceramic jars during fermentation, this study used headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS) to analyze the volatile substances of pickled chilies in ceramic jars from a certain producer after storage for 1–5 years and determined their physicochemical indexes and total bacterial counts. The results showed that the levels of soluble salt-free solids, total acids, total esters, amino nitrogen and total colony count of chopped chili peppers kept changing with storage time, and the quality and aroma kept improving in the first three years, and then the quality declined in the fourth year. A total of 112 volatile compounds were detected, including 22 acids, 12 alcohols, 36 esters, 5 ketones, 9 aldehydes, 5 phenols, 18 hydrocarbons, and 5 other compounds. The volatile composition and content varied with storage time, and 36 volatile compounds with odor activity values (OAVs) greater than 1 were found, which played an important role in the overall aroma of chopped chili peppers. Among them, linalool and methyl salicylate, ethyl salicylate, 4-ethyl-2-methoxyphenol were common to all samples. The samples stored for 1–3 years were superior in terms of organoleptic quality, physicochemical properties and volatile components, while those stored for more than 3 years had a strong aroma but poorer texture.